Algunas consideraciones con miras al fortalecimiento del sistema de inspección del trabajo peruano - De Lama Laura, Manuel Gonzalo (Pontificia Universidad Católica del Perú, 2023)
In this article, the author analyzes and proposes some alternatives with a view to strengthening the Peruvian labor inspection system. In this way, he discusses the exclusion of the inspection procedure from the application of the rules of the general administrative procedure, reviews some criteria of the Committee of the National Superintendence of Labor Inspection-SUNAFIL and, finally, analyzes the non-suspension of the inspection procedure in the case of a related judicial process.

En el presente artículo, el autor analiza y propone algunas alternativas con miras al fortalecimiento del sistema de inspección del trabajo peruano. De esta manera, aborda la exclusión del procedimiento inspectivo de la aplicación de las normas del procedimiento administrativo general, revisa algunos criterios del Comité de la Superintendencia Nacional de Fiscalización Laboral-SUNAFIL y, finalmente, analiza la no suspensión del procedimiento inspectivo en el caso de un proceso judicial vinculado.
Some considerations with a view to strengthening the Peruvian labor inspection system
Keywords: Labor inspection; SUNAFIL; Labor Inspection Court; General Labor Inspection Law; Administrative Sanctions Procedure; Fiscalización laboral; SUNAFIL; Tribunal de Fiscalización Laboral; Ley General de Inspección del Trabajo; Procedimiento Administrativo Sancionador; https://purl.org/pe-repo/ocde/ford#5.05.00